2007
DOI: 10.1007/s00383-007-2011-x
|View full text |Cite
|
Sign up to set email alerts
|

Associated malformations in Morgagni hernia

Abstract: Morgagni hernia (MH) is a congenital herniation of the abdominal organs through the subcostosternal portion of the diaphragm. It is a rare type of diaphragmatic hernia that has been associated with other congenital anomalies. The purpose of this clinical review was to determine the incidence of associated anomalies in patients with MH at a major pediatric referral center. The medical records of all patients with the diagnosis of MH were reviewed retrospectively between 1983 and 2006. The age, sex, side of hern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 18 publications
2
19
1
1
Order By: Relevance
“…6 Berman et al treated only 18 cases of CMH over a period of 40 years and Pokorny et al reported only 4 cases of CMH over a period of 25 years. 8,9 Cigdem et al treated 16 cases of CMH over a period of 23 years. 9 Giovanni Battista Morgagni, an Italian anatomist, first described the herniation of abdominal contents through the sternochondral triangles in 1769 based on cadaver observation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Berman et al treated only 18 cases of CMH over a period of 40 years and Pokorny et al reported only 4 cases of CMH over a period of 25 years. 8,9 Cigdem et al treated 16 cases of CMH over a period of 23 years. 9 Giovanni Battista Morgagni, an Italian anatomist, first described the herniation of abdominal contents through the sternochondral triangles in 1769 based on cadaver observation.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Cigdem et al treated 16 cases of CMH over a period of 23 years. 9 Giovanni Battista Morgagni, an Italian anatomist, first described the herniation of abdominal contents through the sternochondral triangles in 1769 based on cadaver observation. 10 Later, in 1828, Larrey described a surgical approach to the pericardial sac through these same triangles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] The genetic component in the penetrance of MH is further confirmed by the fact that MH is closely associated with Down's syndrome (Trisomy 21). [15,16] These genetic components in the etiology strongly suggest a fusion defect between diaphragmatic muscle fibers and the costochondral arc. [15] Other than genetic factors, mechanical factors such as increased intra-abdominal pressure due to various reasons such as trauma have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] These genetic components in the etiology strongly suggest a fusion defect between diaphragmatic muscle fibers and the costochondral arc. [15] Other than genetic factors, mechanical factors such as increased intra-abdominal pressure due to various reasons such as trauma have been reported. In a multicenter study performed by Al-Salem et al fortyeight infants had MH and 4 were due to acquired etiologies causing increased intra-abdominal pressure such as trauma, ventricul operitoneal shunts, beta thalassemia causing massive splenomegaly, and thus increasing intraabdominal pressure.…”
Section: Discussionmentioning
confidence: 99%